When sports challenge authority : a case study of gatekeeping during the 2017 Chinese ping-pong boycott - Xu, Qingru, active 2018; Billings, Andrew C. (London : Human Kinetics, Inc., 2018)
At the World Tour Platinum China Open in 2017, 3 leading Chinese table tennis players and two coaches withdrew from the Games to protest the sudden removal of Head Coach Liu Guoliang, triggering unprecedented public uproar online. Applying gatekeeping theory, this study explored how mainland Chinese media controlled information flow during the crisis. A thematic analysis uncovered 3 primary gatekeeping behaviors: repetition, selection, and manipulation. Findings suggest that the party-state, not media institutions, was the dominant gatekeeper in mainland China. The Chinese media system and sports system were both subject to strict government control during a crisis that challenged authority.
Originally Published InXu, Q., & Billings, A. (2018). When sports challenge authority: A case study of gatekeeping during the 2017 Chinese ping-pong boycott. International Journal of Sport Communication, 11(4), 529–551.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Mass media policy -- China -- Case studies; Social media in sports -- China -- Case studies